KRAS protein expression becomes progressively restricted during embryogenesis and in adulthood - Minati, Marie-Albane; Assi, Mohamad; Libert, Maxime; Cordi, Sabine; Lemaigre, Frédéric; Jacquemin, Patrick (Frontiers in Cell and Developmental Biology, 2022)
KRAS mutants are common in many cancers and wild-type KRAS is essential in development as its absence causes embryonic lethality. Despite this critical role in development and disease, the normal expression pattern of KRAS protein is still largely unknown at the tissue level due to the lack of valid antibodies. To address this issue, we used the citrine-Kras mouse model in which the Citrine-KRAS (Cit-K) fusion protein functions as a validated surrogate of endogenous KRAS protein that can be detected on tissue sections by immunolabeling with a GFP antibody. In the embryo, we found expression of KRAS protein in a wide range of organs and tissues. This expression tends to decrease near birth, mainly in mesenchymal cells. During transition to the adult stage, the dynamics of KRAS protein expression vary among organs and detection of KRAS becomes restricted to specific cell types. Furthermore, we found that steady state KRAS protein expression is detectable at the cell membrane and in the cytoplasm and that this subcellular partitioning differed among cell types. Our results reveal hitherto unanticipated dynamics in developmental, tissular, cell-specific and subcellular expression of KRAS protein. They provide insight into the reason why specific cell-types are sensitive to KRAS mutations during cancer initiation.